An Experimental Validation of Phase-Based Motion Magnification for Structures with Developing Cracks and Time-Varying Configurations - M. Civera; L. Zanotti Fragonara; P. Antonaci; G. Anglani; C. Surace (Shock and Vibration)
In this study, Computer Vision and Phase-Based Motion Magnification (PBMM) are validated for continuous Structural Health Monitoring (SHM) purposes. The aim is to identify the exact instant of occurrence for damage or abrupt structural changes from video-extracted, very low amplitude (barely visible) vibrations. The study presents three experimental datasets: a box beam with multiple saw cuts of different lengths and angles, a beam with a full rectangular cross section and a mass added at the tip, and the spar of a prototype High-Aspect-Ratio wing. Both mode-shape- and frequency-based approaches are considered, showing the potential to identify the severity and position of the damage as well A high-definition, high-speed camera and a low-cost commercial alternative have been successfully utilised for these video acquisitions. Finally, the technique is also preliminarily tested for outdoor applications with smartphone cameras.